1975
DOI: 10.1090/s0002-9904-1975-13831-6
|View full text |Cite
|
Sign up to set email alerts
|

Finitely embedded modules over Noetherian rings

Abstract: A right R -module is finitely embedded if it has finitely generated essential socle (see, e.g., Vamos [4]). In [1] Jategaonkar settled the Jacobson conjecture for left and right fully bounded noetherian rings by showing that every finitely generated finitely embedded module is artinian. It is an open question whether or not this property holds for an arbitrary left and right noetherian ring (though it is well known that right noetherian is not enough). We prove here that if R is left and right noetherian and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The result announced in [3] follows easily from n v ...,n k eN such that RN = Rn l + ...+Rn k . Thus There is then a right i?-module embedding:…”
Section: Let M R Be a Finitely Generated Non-artinian R-module And Lementioning
confidence: 90%
See 1 more Smart Citation
“…The result announced in [3] follows easily from n v ...,n k eN such that RN = Rn l + ...+Rn k . Thus There is then a right i?-module embedding:…”
Section: Let M R Be a Finitely Generated Non-artinian R-module And Lementioning
confidence: 90%
“…This gives S 2 (CT) s (ST) 2 . Since CT eJ there exists (^ e / such that S 3 C x s (ST)3 . Continuing in this way gives eventually S P B £ (ST) P = 0 for some BeJ.lt follows that S p ^ A.THEOREM 9.…”
mentioning
confidence: 99%
“…It is well known that over a commutative ring, every Noetherian module with essential socle is Artinian. Although this is not true for arbitrary right Noetherian rings, some positive results have been obtained by Ginn and Moss [6] when the ring is right and left Noetherian. Johns [7,Theorem 1], by using a result of Kurshan [8,Theorem 3.3], showed that a right Noetherian ring is right Artinian, provided that every right ideal is a right annihilator.…”
Section: Introductionmentioning
confidence: 96%
“…Although this is not true for arbitrary right Noetherian rings, some positive results have been obtained by Ginn and Moss [6] when the ring is right and left Noetherian. Johns [7,Theorem 1], by using a result of Kurshan [8,Theorem 3.3], showed that a right Noetherian ring is right Artinian, provided that every right ideal is a right annihilator.…”
Section: Introductionmentioning
confidence: 96%